Analisis Prediksi Penjualan Obat Hewan menggunakan Metode Regresi Linier melalui Visualisasi Dashboard (Studi Kasus PT. Satwa Jawa Jaya) - Alya Paramitha Ayuningsih; Nanang Yudi Setiawan; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The process of procuring a product in a distributor company is a long process. Starting from placing an order to the supplier, waiting the order confirmation, the product shipping, until the product can be arrived at the warehouse. Regardless of the lengthy process, companies are required to have a sufficient stock of the products despite uncertain customer demands. It makes companies need to predict future sales. PT. Satwa Jawa Jaya is one of the distributors of animal medication that has a similar problem. Therefore, a sales prediction of the product was made using the Linear Regression method. Predictions were made on 16 products from 7 different suppliers. The results of applying Linear Regression are different for each product. Where the Avatec 20% @ 20 KG product has the highest error rate with 86.25 of MAE score while the Barox Liquid @ 210 Liter product has the lowest error rate with 0,84 of MAE score. Furthermore, in order to facilitate PT. Satwa Jawa Jaya's stakeholders in reading the prediction results, a dashboard consist of visualization was created. Through the usability testing that has been carried out, the dashboard got a Sysem Usability Scale score of 72.5. This shows that the usability level of the dashboard belongs to the good and acceptable category. Which means the dashboard is suitable for use by PT. Satwa Jawa Jaya.